capacitor
Patent Information
- Application Number
- CN202480089454.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-15
- Filing Date
- 2024-09-20
- Publication Date
- 2026-10-09
AI Technical Summary
[0025]根据本公开,可以提供能够兼顾在长时间内维持容量以及抑制内部电阻的上升的电容器。
Smart Images

Figure CN122893173A_ABST
Abstract
Description
[0001] Cross-reference of related applications
[0002] This disclosure claims the benefit of priority to Japanese Patent Application No. 2024-041389, filed with the Japan Patent Office on March 15, 2024, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] This invention relates to capacitors. Background Technology
[0004] Double-layer capacitors, for example, comprise a first electrode, a second electrode, and an electrolyte. In these capacitors, at least one of the first and second electrodes contains an electrode active material, typically porous carbon particles such as activated carbon. Various modifications to porous carbon particles such as activated carbon have been investigated in such capacitors.
[0005] Patent Document 1 describes a double-layer capacitor comprising: a pair of polarized electrodes, each comprising activated carbon and a capping layer made of silicon oxide or a metal oxide formed on at least a portion of the surface of the activated carbon; a metal current collector; a separator disposed between the polarized electrodes; and an electrolyte. Furthermore, Patent Document 1 describes that, as described above, by forming a capping layer made of silicon oxide or a metal oxide on at least a portion of the surface of the activated carbon, the voltage withstand capability of the double-layer capacitor can be improved and its capacitance can be maintained even after continuous treatment with an applied voltage of 3.0V to 3.5V for 1000 hours.
[0006] Patent Document 2 describes an electrochemical capacitor using a polarized electrode formed from a composition containing activated carbon and an organic electrolyte. The activated carbon used satisfies the condition that the ratio of (pore size with diameter of 40-100 nm) to (total pore size in BJH) is 0.1 or higher. The document also describes a method of treating the activated carbon with low-temperature plasma containing carbon dioxide gas to obtain activated carbon with the aforementioned properties. Furthermore, Patent Document 2 describes that, compared to commercially available activated carbon, the activated carbon satisfying the above conditions has a higher proportion of pores with diameters of 40-100 nm, thus improving the reactivity of electrolyte ions from the organic electrolyte with the polarized electrode. Moreover, Patent Document 2 describes that, by increasing the reactivity of electrolyte ions with the polarized electrode, the activated carbon satisfying the above conditions has approximately 1.5 times higher electrostatic capacitance compared to commercially available activated carbon.
[0007] Patent Document 3 describes a double-layer capacitor consisting of electrodes and an electrolyte, in which supercritical activated carbon, washed with water at a temperature above 300°C and a pressure of 23-30 MPa, is used as the activated carbon. The electrodes are made of activated carbon with clamping separators. Furthermore, Patent Document 3 describes that in the activated carbon described above, pore shrinkage is suppressed, and impurities and functional groups present in the pores are effectively removed. Moreover, Patent Document 3 describes that even after continuously applying a voltage of 2.7V for 1000 hours to a double-layer capacitor using the activated carbon described above, the electrostatic capacitance can be maintained, and the increase in resistivity can be suppressed.
[0008] Patent Document 4 discloses an activated carbon for electrode materials, characterized in that it is composed of porous activated carbon having mesopores and macropores, and is used as an electrode material for an energy storage device, wherein at least a portion of the macropores is covered by a conductive polymer material. Furthermore, Patent Document 4 discloses an energy storage device in which the aforementioned activated carbon for electrode materials is used in the conductive material layer of at least one of the positive and negative electrodes. Moreover, Patent Document 4 discloses that, as described above, in activated carbon where at least a portion of the macropores is covered by a conductive polymer material, ions can be chemically adsorbed through the redox reaction of the conductive polymer material, thus effectively increasing the adsorption of ions into the macropores, resulting in an increase in the initial discharge capacity of the energy storage device. Additionally, Patent Document 4 discloses that, due to the presence of the conductive polymer, the conductivity of the activated carbon surface is increased, thereby further reducing its resistance value, resulting in a reduction in the initial internal resistance of the energy storage device.
[0009] Existing technical documents
[0010] Patent documents
[0011] Patent Document 1: Japanese Patent Application Publication No. 9-63905
[0012] Patent Document 2: Japanese Patent Application Publication No. 2010-114356
[0013] Patent Document 3: Japanese Patent Application Publication No. 2004-31713
[0014] Patent Document 4: Japanese Patent Application Publication No. 2010-003940 Summary of the Invention
[0015] The problem the invention aims to solve
[0016] In the aforementioned Patent Document 1, although the capacitance maintenance of the double-layer capacitor over a long period of time (e.g., 1000 hours) was studied, no study was conducted on suppressing the increase of the internal resistance of the double-layer capacitor over a long period of time.
[0017] In the aforementioned Patent Document 2, although the initial capacity of the electrochemical capacitor was studied, no study was conducted on maintaining the capacity of the electrochemical capacitor over a long period of time or suppressing the increase in internal resistance.
[0018] In the aforementioned patent document 3, a study was conducted on maintaining the capacitance of the double-layer capacitor over a long period of time and suppressing the increase in resistivity. Although it was possible to maintain the capacitance (approximately 80% of the initial capacitance), it could not be said that the suppression of the increase in resistivity (approximately 150% of the initial resistivity) was sufficiently achieved.
[0019] In the aforementioned Patent Document 4, although studies were conducted on increasing the initial discharge capacity and reducing the initial internal resistance in the energy storage device, no studies were conducted on maintaining the capacity over a long period of time and suppressing the rise in internal resistance.
[0020] Thus, in capacitors, it cannot be said that sufficient research has been conducted on balancing the maintenance of capacitance over a long period of time with the suppression of the rise in internal resistance.
[0021] Therefore, the objective of this disclosure is to provide a capacitor that can maintain capacitance over a long period of time while suppressing the rise of internal resistance.
[0022] Solution for solving the problem
[0023] One aspect of the present invention relates to a capacitor comprising a first electrode, a second electrode, and an electrolyte, wherein at least one of the first electrode and the second electrode comprises at least a portion of porous carbon particles covered by a nitrogen-containing carbon material as an electrode active material, the nitrogen-containing carbon material comprising a 6-membered ring, the 6-membered ring comprising at least one of one or more carbonyl carbons and two or more nitrogen atoms, the porous carbon particles covered by the nitrogen-containing carbon material having micropores with a pore size of 0.7 nm or more and 2 nm or less, and first mesopores with a pore size of more than 2 nm and 5 nm or less, wherein the ratio of the first mesopore volume PV2 to the micropore volume PV1 (PV2 / PV1) is greater than 0.57.
[0024] The effects of the invention
[0025] According to this disclosure, a capacitor can be provided that can maintain capacitance over a long period of time while suppressing the rise of internal resistance.
[0026] The novel features of the invention are set forth in the claims, but the invention relates to both its structure and content, and will be better understood, together with other objects and features of the invention, by reference to the following detailed description of the accompanying drawings. Attached Figure Description
[0027] Figure 1 This is a partial cross-sectional perspective view of an organic electrolyte double-layer capacitor according to one embodiment of the present disclosure.
[0028] Figure 2 The micropore volume distribution of the porous carbon particles covered in Examples 1-2 and Comparative Examples 1-5 is shown. Detailed Implementation
[0029] The following examples illustrate embodiments of this disclosure, but this disclosure is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes cited, but other numerical values, materials, etc., can also be applied as long as the effects of this disclosure can be achieved. It should be noted that the constituent elements of the characteristic portions of this disclosure can also utilize known constituent elements. In this specification, when referring to "the range of numerical values A to B," this range includes both numerical values A and B.
[0030] In the following explanation, when lower and upper limits of values related to specific physical properties, conditions, etc., are given as examples, any of the examples of lower limits can be arbitrarily combined with any of the examples of upper limits, as long as the lower limit is not greater than or equal to the upper limit. When multiple materials are given as examples, unless otherwise specified, one can be selected and used alone, or two or more can be combined.
[0031] This disclosure includes a combination of the contents of two or more claims selected from the plurality of claims in the appended claims. That is, it is possible to combine the contents of two or more claims selected from the plurality of claims in the appended claims, provided that no technical contradiction is created.
[0032] The capacitor in the embodiments of this disclosure includes a first electrode, a second electrode, and an electrolyte. The term "capacitor" can also be replaced with "condenser." A capacitor refers, for example, to an energy storage device such as an electric double-layer capacitor or a lithium-ion capacitor.
[0033] In the capacitor of the embodiments of this disclosure, at least one of the first electrode and the second electrode comprises porous carbon particles covered by at least a portion of a nitrogen-containing carbon material as the electrode active material. In the capacitor of the embodiments of this disclosure, the nitrogen-containing carbon material comprises a 6-membered ring and covers at least a portion of the porous carbon particles. In the capacitor of the embodiments of this disclosure, the porous carbon particles covered by at least a portion of the nitrogen-containing carbon material have micropores with a pore size of 0.7 nm or more and 2 nm or less, and first mesopores with a pore size exceeding 2 nm and less than 5 nm, wherein the ratio of the first mesopore volume PV2 to the micropore volume PV1 (PV2 / PV1) exceeds 0.57. It should be noted that, hereinafter, the porous carbon particles covered by at least a portion of the nitrogen-containing carbon material are also referred to as covered porous carbon particles. Furthermore, hereinafter, the electrode comprising covered porous carbon particles as the electrode active material is also referred to as electrode (E). It can be said that covered porous carbon particles are particles comprising porous particles and at least a portion of a nitrogen-containing carbon material covering their surface. That is, the porous carbon particles can also be particles with a core-shell structure, where the porous carbon particles form the core and the nitrogen-containing carbon material forms the shell. The boundary between the porous carbon particles and the nitrogen-containing carbon material can be indistinct, and there can be a region that possesses the intermediate structure and physical properties of both.
[0034] In the case of a double-layer capacitor in the embodiments of this disclosure, ions are adsorbed onto the porous carbon particles in the electrolyte, thereby forming an electric double layer between the porous carbon particles and the electrolyte. This results in capacitance in the double-layer capacitor. Furthermore, if ions desorb from the porous carbon particles, a non-Radial current flows. That is, in the case of a double-layer capacitor in the embodiments of this disclosure, the double layer is formed during charging and disappears during discharging.
[0035] In the capacitor of the present disclosure, it is important to use covered porous carbon particles as the electrode active material, wherein the ratio of the first mesopore volume PV2 to the micropore volume PV1 (PV2 / PV1) is greater than 0.57. The reasons for this will be explained below.
[0036] Porous carbon particles such as activated carbon typically possess hydrophilic acidic functional groups (e.g., carboxyl, hydroxyl, quinone, phenolic hydroxyl, etc.) on their surface (the inner wall of the pores). Furthermore, these hydrophilic acidic functional groups, as described above, become reactive sites for ions contained in the electrolyte. Therefore, for example, ions in the electrolyte adsorb onto the hydrophilic acidic functional groups, thereby reducing the ion concentration in the electrolyte and sometimes increasing the internal resistance of the capacitor. Additionally, the internal resistance of the capacitor may also increase due to chemical reactions between the acidic functional groups and the ions in the electrolyte. To mitigate this effect, for example, materials capable of doping and dedoping with ions can be considered to cover the hydrophilic acidic functional groups. However, in the case of covering the hydrophilic acidic functional groups, if the micropores (pore diameter less than 2 nm) and mesopores (pore diameter greater than 2 nm but less than 50 nm) present in the porous carbon particles become too small or collapse, ion migration / diffusion becomes difficult within the porous carbon particles, leading to an increase in the internal resistance of the capacitor. Furthermore, after the hydrophilic acidic functional groups are covered, if the micropore volume and mesopore volume are not properly balanced, ion migration will be difficult to occur inside the porous carbon particles and consequently inside the capacitor electrodes, leading to an increase in the capacitor's internal resistance. Furthermore, if ion migration is difficult to occur inside the electrodes, it will be difficult to maintain the capacitance over a long period (e.g., 1000 hours). Therefore, a proper balance between micropore volume and mesopore volume is required to create hierarchical pores.
[0037] However, as explained above, in the capacitor of the present disclosure, as the electrode active material, covered porous carbon particles with a first mesopore volume PV2 to micropore volume PV1 ratio (PV2 / PV1) exceeding 0.57 are used; that is, covered porous carbon particles in which the micropore volume and mesopore volume are appropriately balanced. Therefore, it is possible to suppress the reduction of pores while covering hydrophilic acidic functional groups, and to facilitate the migration of ions inside the porous carbon particles and inside the capacitor electrode. As a result, the internal resistance of the capacitor can be sufficiently reduced. In addition, the capacitance can be maintained for a long time.
[0038] The ratio of PV2 / PV1 is preferably 0.58 or higher, more preferably 0.60 or higher, and even more preferably 0.62 or higher. The ratio of PV2 / PV1 is typically 5 or lower. It should be noted that the micropore volume PV1 and the first mesopore volume PV2 can be calculated from the differential micropore volume distribution of the porous carbon particles, as described later.
[0039] Here, in the process of covering porous carbon particles, as described below, at least a portion of the nitrogen-containing carbon material covering the porous carbon particles is obtained by carbonizing the raw material of the nitrogen-containing carbon material at a high temperature. Furthermore, such raw materials are mostly resins with cross-linked structures, and are mostly carbonized in the form of a mixture with porous carbon particles. Additionally, when obtaining the mixture as described above, the resin with cross-linked structures is usually diluted with an organic solvent and mixed with the porous carbon particles. Therefore, PV2 / PV1 can be adjusted, for example, by the concentration of the resin with cross-linked structures in the organic solvent. Specifically, by increasing the concentration of the resin with cross-linked structures in the organic solvent, PV2 / PV1 can be reduced, and by decreasing the concentration of the resin with cross-linked structures in the organic solvent, PV2 / PV1 can be increased. It should be noted that the concentration of the resin with cross-linked structures in the organic solvent is preferably less than 2% by mass, more preferably 1.5% by mass or less, and even more preferably 1.0% by mass or less. If the concentration of the resin with cross-linked structures in the organic solvent is too high, the viscosity of the organic solvent containing the resin with cross-linked structures is too high, and therefore the resin with cross-linked structures tends to be concentrated in a portion of the porous particles. As a result, in capped porous carbon particles, micropores and mesopores can sometimes become too small or collapse. Furthermore, in capacitors containing such capped porous carbon particles as electrode active materials, it is sometimes impossible to simultaneously maintain capacitance over long periods and suppress the rise in internal resistance.
[0040] (Porous carbon particles)
[0041] Porous carbon particles can be produced, for example, by heat-treating a carbonaceous raw material to obtain a carbide, and then activating the carbide to make it porous. Examples of porous carbon particles include activated carbon, but are not limited to this. When producing porous carbon particles, the ratio (PV2 / PV1) of the micropore volume PV1 (with a pore size of 0.7 nm or more and 2 nm or less) to the first mesopore volume PV2 (with a pore size exceeding 2 nm and less than 5 nm) is sufficient to be greater than 0.57. Examples of carbonaceous raw materials include wood, coconut shells, pulp waste liquid, coal, coal-based pitch obtained through the thermal decomposition of coal, heavy oil, petroleum-based pitch obtained through the thermal decomposition of heavy oil, phenolic resin, petroleum coke, and coal coke. Examples of activation treatments include gas activation using gases such as water vapor and chemical activation using alkalis such as potassium hydroxide. Porous carbon particles can be porous carbon particles that have undergone pulverization. Porous carbon particles can be graded after pulverization. Crushing processes can be carried out using, for example, ball mills or spray mills.
[0042] Porous carbon particles can be obtained, for example, by pulverizing and granulating carbonized materials obtained from heat-treated coconut shells, followed by activation treatment of the pulverized and granulated particles. Porous carbon particles can also be obtained, for example, by adding a binder such as coal tar or pitch to finely pulverized coal and mixing it to obtain a compound, compressing the compound to obtain a molded product, pulverizing and granulating the molded product, and then activating the pulverized and granulated particles.
[0043] The pore distribution of porous carbon particles can be adjusted by the type of carbonaceous raw material, heat treatment temperature, activation temperature, and degree of pulverization. Porous carbon materials can be used alone or in combination of two or more types.
[0044] Porous carbon particles are typically granular. The average particle size of porous carbon particles is, for example, greater than 1 μm and less than 20 μm. Alternatively, the average particle size can be greater than 3 μm and less than 15 μm. It should be noted that the average particle size refers to the particle size that constitutes 50% of the total volume in a volumetric particle size distribution determined by laser diffraction / scattering.
[0045] The specific surface area A of porous carbon particles is, for example, 1200–2500 m². 2 / g. Specific surface area A can be 1350–2300 m². 2 / g. By making the specific surface area A 1200m² 2 Specific surface areas above a certain size (e.g.) tend to exhibit high capacity. This is achieved by setting the specific surface area A to 2500 m². 2 With a specific surface area of less than 1 g, the contact area with the electrolyte can be reduced, thus suppressing the decomposition of the electrolyte accompanied by side reactions. The specific surface area A can be measured, for example, using a BELSORP 28SA available from BEL Corporation of Japan. Specifically, the measurement can be performed according to the following steps.
[0046] <Steps>
[0047] (1) Collect a sample of porous carbon particles of 0.20 g to 0.25 g, place the sample in a measuring cell made of a glass tube for measuring specific surface area, and perform drying and degassing in the measuring cell. The drying and degassing is carried out at a pressure of 6.67 Pa and a temperature of 250 ± 5 °C for more than 1 hour.
[0048] (2) The mass of the sample in the measuring cell is measured to the order of 0.1 mg.
[0049] (3) The nitrogen adsorption amount of the sample at a temperature of -196℃ was determined using the above-mentioned measuring device.
[0050] (4) Based on the adsorption amount measurement results, the specific surface area A is determined using the BET multi-point method within the range of partial pressure (relative pressure) of 0.001 to 0.2. Specifically, the specific surface area A is determined within the range of the above partial pressure (relative pressure) and the area within which a straight line is drawn.
[0051] (Nitrogen- and carbon-containing materials)
[0052] As described above, the nitrogen-containing carbon material comprises a 6-membered ring. The 6-membered ring comprises at least one of one or more carbonyl carbon atoms and two or more nitrogen atoms. The 6-membered ring may contain carbon atoms bonded to two nitrogen atoms. The 6-membered ring may form a conjugated system relating to all six atoms constituting the 6-membered ring. The 6-membered ring may comprise both one or more carbonyl carbon atoms and two or more nitrogen atoms. A 6-membered ring comprising both carbonyl carbon and nitrogen atoms may be a 6-membered ring comprising two or three carbonyl carbon atoms and two or three nitrogen atoms. The 6-membered ring may have a 1,3,5-trione ring, a triazine ring, or a structure comprising both a 1,3,5-trione ring and a triazine ring (e.g., an isocyanurate ring). The 6-membered ring may comprise at least one element selected from the group consisting of an isocyanurate ring, a triazine ring, and a 1,3,5-trione ring.
[0053] The six-membered ring is a structure derived from the raw materials of nitrogen-containing carbon materials. On the other hand, nitrogen-containing carbon materials are manufactured by carbonizing the raw materials at high temperatures. Therefore, the structure of the six-membered ring is sometimes not clearly detectable within porous carbon particles. Even in such cases, the nitrogen-containing carbon material or its raw materials can be identified using structural analysis combining FT-IR and XPS, or by the methods described in JIS M8813:2004. It should be noted that the methods described in JIS M8813:2004 can be performed using an oxygen, nitrogen, and hydrogen analyzer (e.g., the "EGMA-830 type" manufactured by Horiba Manufacturing Co., Ltd.).
[0054] The six-membered ring exhibits excellent structural stability. This superior structural stability is believed to contribute to improved reliability in capacitors such as electric double-layer capacitors. The nitrogen atoms in the six-membered ring are thought to contribute to the excellent initial capacitance or reduced low-temperature resistance of the capacitor. This contribution is speculated to be related to the presence of carbon atoms bonded to the two nitrogen atoms constituting the six-membered ring. It is believed that nitrogen-containing carbon materials not only readily exhibit pseudo-capacitance accompanied by Faraday reactions, but also that this pseudo-capacitance is highly reversible.
[0055] The 6-membered ring preferably contains an isocyanurate ring. The isocyanurate ring exhibits excellent structural stability. The isocyanurate ring contains three carbonyl carbons bonded to two nitrogen atoms. The isocyanurate ring is particularly stable in environments with low moisture or protic solvent content.
[0056] The 6-membered ring preferably contains a triazine ring. Triazine rings exhibit excellent structural stability. The triazine ring contains three carbon atoms bonded to two nitrogen atoms. Triazine rings are particularly stable in environments with low moisture or protic solvent content.
[0057] The 6-membered ring can be bonded with an aromatic ring as a substituent. The aromatic ring as a substituent can be bonded to the 1, 3, and 5 positions of the 6-membered ring, respectively. The aromatic ring as a substituent can be phenyl. The phenyl group can further have substituents. The substituents bonded to the phenyl group can be C1-C6 alkyl groups such as methyl, ethyl, and propyl, or C1-C6 alkenyl groups.
[0058] Nitrogen-containing carbon materials can further include 1,3,5-triketone rings (hereinafter referred to as triketone rings). It is believed that the double oxygen bonds in the triketone ring contribute to excellent initial capacitance or reduced low-temperature resistance in capacitors. Triketone rings exhibit excellent structural stability, are low in moisture or protic solvents, and are particularly stable in environmental conditions.
[0059] The isocyanuride ring contains three carbon atoms bonded to two nitrogen atoms and is also a triketone ring. Therefore, nitrogen-containing carbon materials containing the isocyanuride ring are also useful as electrode active materials.
[0060] Nitrogen-containing carbon materials can be prepared or manufactured, for example, using polyisocyanates as raw materials. The polyisocyanates preferably have aromatic rings. Toluene diisocyanate is used to form a cross-linked polymer with an isocyanurate ring via a trimerization reaction as shown below. The isocyanurate ring of the cross-linked polyisocyanate with aromatic rings has an aromatic ring bonded to a nitrogen atom as a substituent. Such cross-linked polymers are suitable as raw materials for nitrogen-containing carbon materials with excellent structural stability.
[0061]
[0062] By adding polyols to polyisocyanates or toluene diisocyanates, cross-linked materials with excellent thermal decomposition properties (easy carbonization) can be generated. Heating these easily carbonized cross-linked materials under an inactive atmosphere allows for the low-cost production of desired nitrogen-containing carbon materials.
[0063] As a polyol, a structure that readily forms spaces between the isocyanuride rings is preferred, such as glycerol, triglycerides, polyalkylene glycols, and alkylene glycols (HO-(CH2)). n -OH), etc. Alkanediols (HO-(CH2)) n The number of carbon atoms (n) in the -OH group can be, for example, 2 to 10. The isocyanate group reacts with the alcoholic hydroxyl group to form an urethane bond. A flexible linking group can be formed within the crosslinked body via the urethane bond. For example, when using an alkanediol, the linking group has -(CH2). n - structure.
[0064] The amount of polyol added to the polyisocyanate can be appropriately selected. The amount of polyol added is, for example, based on 100 to 1000 parts by weight, 200 to 700 parts by weight, or 250 to 500 parts by weight relative to 100 parts by weight of the polyisocyanate. Since polyisocyanates are expensive, it is preferable to increase the proportion of polyol in terms of cost.
[0065] The crosslinked body described above is carbonized in an inactive atmosphere as a mixture with porous carbon material. By carbonizing the crosslinked body in this way, it is possible to obtain an electrode active material (i.e., a material covering porous carbon particles) in which at least a portion of the porous carbon particles is covered by a nitrogen-containing carbon material. The inactive atmosphere can be any non-oxidizing atmosphere, such as a reduced pressure atmosphere (e.g., below 0.1 MPa (preferably below 10 Pa)), a reducing atmosphere (e.g., a hydrogen atmosphere below 0.01 MPa), or an inactive gas atmosphere (e.g., a flowing atmosphere such as N2, Ar, Ne, and He).
[0066] The heating temperature of the above mixture is preferably below 800°C. The heating temperature can be below 750°C. If the heating temperature exceeds 800°C, the resulting porous carbon particles will contain nitrogen at a content of C. N There is a tendency for the number of six-membered rings to become too low, or to excessively reduce the number of six-membered rings containing at least one carbonyl carbon and at least one nitrogen atom.
[0067] The heating time can be selected appropriately according to the heating conditions. For example, the heating time can be set to about 0.5 to 5 hours.
[0068] (Covered with porous carbon particles)
[0069] Covered porous carbon particles function as electrode active materials exhibiting capacity through doping and dedoping with ions. Doping of covered porous carbon particles encompasses concepts such as ion adsorption into the particles, ion storage by the particles, and chemical interactions between the particles and ions. Dedoping of covered porous carbon particles includes concepts such as ion desorption, ion release, and elimination of chemical interactions between the particles and ions. It should be noted that both the porous carbon particles and the nitrogen-containing carbon material possess the function of doping and dedoping with ions in covered porous carbon particles. That is, capacity is exhibited in covered porous carbon particles through doping and dedoping with ions in both the porous carbon particles and the nitrogen-containing carbon material.
[0070] Here, ion doping into the porous carbon particles mainly refers to the adsorption of ions into the porous carbon particles, while ion dedoping from the porous carbon particles mainly refers to the desorption of ions from the porous carbon particles. As explained above, if ions are adsorbed onto the porous carbon particles, an electrical double layer is formed, exhibiting capacity. That is, as described below, the active layer (electrode layer) formed from the slurry containing the porous carbon particles functions as a polarizing electrode. However, the active layer (electrode layer) can also be a layer where the Faraday reaction contributes to capacity.
[0071] The porous carbon particles are preferably covered with a micropore volume PV1 of 0.42 mL / g or more and a first mesopore volume PV2 of 0.25 mL / g or more. The micropore volume PV1 is more preferably 0.43 mL / g or more, and even more preferably 0.44 mL / g or more. The micropore volume PV1 is preferably 1.5 mL / g or less, and even more preferably 1.2 mL / g or less. The first mesopore volume PV2 is more preferably 0.32 mL / g or more, and even more preferably 0.35 mL / g or more. The first mesopore volume PV2 is preferably 2.0 mL / g or less, and even more preferably 1.5 mL / g or less. By keeping the micropore volume PV1 and the first mesopore volume PV2 within the aforementioned ranges, when used as an electrode active material in a capacitor, it is easy to maintain capacitance over a long period and suppress the increase in internal resistance in the capacitor.
[0072] For porous carbon particles, the ratio of the second mesopore volume PV3 to the total pore volume PVT (PV3 / PVT) with a fine pore size greater than 2 nm and less than 50 nm is preferably greater than 0.36. PV3 / PVT is more preferably 0.37 or more, more preferably 0.38 or more. PV3 / PVT is preferably 5 or less, more preferably 3 or less. By keeping PV3 / PVT within the above-mentioned range, when used as an electrode active material in a capacitor, it is easy to maintain capacitance over a long period of time and suppress the increase of internal resistance in the capacitor.
[0073] The differential pore volume distribution covering porous carbon particles can be determined, for example, by analyzing adsorption isotherms measured using a nitrogen-based gas adsorption method via the BJH (Barrett-Joyner-Hallenda) method or the DFT (Density Functional Theory) method. The total pore volume is the cumulative value of the pore volume within the differential pore volume distribution obtained through the BJH method.
[0074] When the porous carbon particles are derived from at least one of the first and second electrodes taken from a capacitor, the sample used for determining the differential pore volume distribution is preferably a sample obtained by immersing the porous carbon particles in a highly volatile solvent (e.g., dimethyl carbonate), washing it under reduced pressure less than 0.1 MPa, and then drying it under reduced pressure less than 0.1 MPa for at least 2 hours. Drying can be carried out, for example, at room temperature (23 ± 2 °C).
[0075] The differential pore volume distribution of porous carbon particles can be measured, for example, using a BELSORP 28SA apparatus available from BEL Corporation of Japan. As an analytical theory for mesopores, the Dolimore Heal method (DH method) based on capillary condensation theory (Kelvin's formula) can be used. Alternatively, the differential pore volume distribution of micropores can be analyzed using the MP method (R.SH.MICHAi Letal., J.Coll.Inter.Sci., 26(1968)45). In the MP method, assuming the pores have a slit shape, the sum of the volumes of pores with that slit width can be calculated as a function of the slit width. Alternatively, the pore volume distribution can also be calculated using the DFT method. The DFT method, also known as molecular dynamics simulation, is a method for analyzing adsorption phenomena based on statistical and thermodynamic theories at the molecular level. An autosorb-iQ apparatus manufactured by Anton Paar can be used as the apparatus.
[0076] The porous carbon particles covering the surface preferably have a diameter of 1650 μm. 2 A specific surface area A1 of / g or higher. A more preferably, a specific surface area A1 is 1700m². 2 / g or more, preferably 1800m 2 / g or more. Specific surface area A1 is more preferably 2600 m². 2 / g or less, more preferably 2500m 2 / g or less. By keeping the specific surface area A1 within the range described above, when using it as an electrode active material in a capacitor, it is easy to maintain capacitance over a long period of time and suppress the increase in internal resistance. The specific surface area A1 can be measured in the same way as the specific surface area A.
[0077] The porous carbon particles covering the electrode preferably exhibit the following characteristics: a first peak in the microporous volume distribution exceeding 0 nm but less than 1 nm, a second peak in the range of 1 nm to 2 nm, and a third peak in the range of 2 nm to 5 nm. The presence of such small pores facilitates ion migration within the porous carbon particles and subsequently within the electrode. Preferably, in the microporous volume distribution, the peak apex P1 of the first peak is located at 1.5 cm⁻¹. 3In the range above / (g·nm), the peak P2 of the second peak is located at 1.0 cm. 3 In the range above / (g·nm), the peak P3 of the third peak is located at 1.3cm. 3 The range is above / (g·nm). The porous carbon particles exhibit the aforementioned characteristics in the differential fine pore volume distribution, thereby creating a hierarchical fine pore volume distribution that easily forms an environment favorable for the migration of ions within the porous carbon particles and, consequently, within the electrode.
[0078] Peak P1 can be located at 1.6 cm. 3 The range above / (g·nm) can also be located at 1.7cm. 3 The range is above / (g·nm). The peak P1 can be located at 3.5cm. 3 The range below / (g·nm) can also be located at 3.2cm. 3 The range is below / (g·nm). The peak P2 can be located at 1.1cm. 3 The range is above / (g·nm). The peak P2 can be located at 2.0 cm. 3 The range below / (g·nm) can also be located within 1.8cm. 3 The range is below / (g·nm). The peak P3 can be located at 1.4 cm. 3 The range above / (g·nm) can also be located within 1.5cm. 3 The range is above / (g·nm). The peak P3 can be located at 2.5cm. 3 The range below / (g·nm) can also be located at 2.2cm. 3 The range below / (g·nm).
[0079] When the porous carbon particles are distributed in a microporous volumetric pattern, and the heights of peak P1, P2, and P3 are set as HP1, HP2, and HP3 respectively, HP1, HP2, and HP3 preferably satisfy the relationship HP1>HP3>HP2. By satisfying this relationship, an environment conducive to ion migration within the electrode can be easily formed.
[0080] The porous carbon particles can also exhibit at least one peak above 50 nm in the micropore volume distribution. That is, the porous carbon particles can also possess macropores. By making the porous carbon particles macropores, the micropore volume distribution can be further hierarchically structured. This facilitates the formation of an environment more favorable for ion migration within the electrode.
[0081] In the porous carbon particles covered with nitrogen content C N Preferably less than 3% by mass. Nitrogen content C N It can be less than 2% by mass. Nitrogen content CN It can be 0.15% by mass or more, or 1% by mass or more. This is achieved by adjusting the nitrogen content C... N Within the numerical range described above, the content of 6-membered rings containing two or more nitrogen atoms can be set to an appropriate range. Therefore, on the surface of porous carbon particles such as activated carbon, the reaction between the aforementioned hydrophilic acidic functional groups and electrolyte ions can be further suppressed. As a result, the increase in internal resistance can be suppressed. Furthermore, since ion migration / diffusion is readily generated, the increase in internal resistance can also be suppressed.
[0082] In the porous carbon particles covered with oxygen content C O Preferably less than 6% by mass. Oxygen content C O It can be below 5% by mass. Oxygen content C O It can be 1% or more by mass, or 3% or more by mass. This is achieved by increasing the oxygen content C... O Within the numerical range described above, the content of the triketone ring can be kept within an appropriate range. Therefore, on the surface of porous carbon particles such as activated carbon, the reaction between the aforementioned hydrophilic acidic functional groups and electrolyte ions can be further suppressed. As a result, the increase in internal resistance can be suppressed. Furthermore, due to the ease with which ion migration / diffusion occurs, the increase in internal resistance can also be suppressed.
[0083] <Organic Electrolyte>
[0084] Organic electrolytes contain non-aqueous solvents and organic salts dissolved in the non-aqueous solvents. Non-aqueous solvents refer to solvents other than water, including organic solvents. Organic salts are salts in which at least one of the anion and cation contains an organic compound. Examples of the concentration of organic salts in organic electrolytes include 0.5–2.0 mol / L. Compared to aqueous electrolytes, organic electrolytes have a wider potential window (voltage withstand capability), enabling higher voltage withstand capabilities and significantly contributing to improved energy density and output power density of capacitors.
[0085] The non-aqueous solvent is preferably a high-boiling-point solvent. Examples of high-boiling-point solvents include lactones such as γ-butyrolactone; carbonates such as propylene carbonate; polyols such as ethylene glycol and propylene glycol; cyclic sulfones such as sulfolane; amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone; esters such as methyl acetate; ethers such as 1,4-dioxane; ketones such as methyl ethyl ketone; and aldehydes such as formaldehyde. From the viewpoint of improving the structural stability of the porous carbon particles, aprotic solvents are preferred. The non-aqueous solvent preferably contains 80% by mass or more of aprotic solvent.
[0086] Organic salts containing organic matter as cations include, for example, onium salts such as quaternary ammonium salts. Organic salts containing organic matter as anions (or zwitterions) include, for example, salts of carboxylic acids and onium salts (carboxylic onium salts). Examples of carboxylic onium salts include trimethylamine maleate, triethylamine borosalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazoline onium phthalate, and mono-1,3-dimethyl-ethylimidazoline onium phthalate. These organic salts are believed to not only contribute to increasing the polarity of organic electrolytes and improving wettability to porous carbon particles, but also to enhance pseudocapacity through redox reactions originating from nitrogen atoms contained in the organic salt. Furthermore, they may also increase carrier concentration at the interface between carbon material (NC) and the organic electrolyte, improve space charge capacity, and induce charge bias within the carbon hexagonal facets.
[0087] From the viewpoint of improving voltage withstand characteristics, the anion preferably contains a fluorine atom. For example, BF4 is used as an anion. - and PF6 - And so on. Anions containing these fluorine atoms can be used alone or in combination of two or more. Preferred organic salts include, for example, tetraalkylammonium salts such as ethyltrimethylammonium tetrafluoroborate and triethylmethylammonium tetrafluoroborate.
[0088] Organic electrolytes may contain trace amounts of water. However, from the viewpoint of improving the structural stability of the porous carbon particles, the water content of the organic electrolyte is preferably below 50 ppm by mass.
[0089] (Electrode (E))
[0090] The electrode (E) may include an active layer and a current collector supporting the active layer. The current collector is not particularly limited, and known current collectors used in electrodes of electrochemical devices can be used. As the current collector, metal foil, porous metal bodies, etc., can be used. As the material of the current collector, aluminum, copper, nickel, iron, stainless steel, platinum, etc., can be used. As the material of the current collector, alloys with the above-mentioned metals as the main components can be used. As the metal foil, plain foil, foil roughened by etching or other methods, foil subjected to plasma treatment, etc., can be used. Porous metal bodies, for example, have a three-dimensional network structure.
[0091] The electrode (E) may also contain any components such as binder and conductive additives. The binder serves to assist in the bonding between porous carbon particles and the bonding between porous carbon particles and the current collector.
[0092] Examples of adhesive materials include fluoropolymers such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), and PVdF-HFP copolymer, as well as water-soluble resins such as carboxymethyl cellulose (CMC), polyethylene oxide (PEO), polyethylene glycol (PEG), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyacrylic acid (PAA), and polyvinyl acetate.
[0093] Examples of conductive additives include carbon black and carbon fiber. Carbon black is preferred as a conductive additive. Examples of carbon black include acetylene black and Ketjen black.
[0094] The electrode (E) can be manufactured, for example, by dispersing porous carbon particles and any component (binder, conductive additive, etc.) together in a dispersion medium such as water to obtain a slurry, coating the slurry onto a current collector to obtain a coating film, and drying the coating film to obtain an active layer (electrode layer). That is, the electrode (E) can be fabricated, for example, as an electrode having a current collector and an active layer (electrode layer) disposed on the current collector. It should be noted that, from the viewpoint of further improving the adhesion to the current collector, the active layer (electrode layer) can also be calendered.
[0095] (Capacitor)
[0096] Next, an example of a capacitor having an electrode (E) will be described. Figure 1 This is a partially cross-sectional three-dimensional view of an electric double-layer capacitor (EDLC(NC)) with an organic electrolyte.
[0097] The EDLC(NC) 10 shown in the figure includes a wound capacitor element 1. The capacitor element 1 is constructed by winding a first electrode 2 and a second electrode 3, which are respectively sheet-shaped electrodes (E), with a separator 4 in between.
[0098] The first electrode 2 has a first current collector and a first active layer containing porous carbon particles loaded on the surface of the first current collector, exhibiting capacity through ion adsorption and desorption. The second electrode 3 has a second current collector and a second active layer containing porous carbon particles loaded on the surface of the second current collector, exhibiting capacity through ion adsorption and desorption. Aluminum foil is used, for example, as the first and second current collectors. The surfaces of the first and second current collectors can be roughened by methods such as etching.
[0099] The separator 4 is, for example, made of a nonwoven fabric with cellulose as the main component. Leads 5a and 5b, serving as lead-out members, are connected to the first electrode 2 and the second electrode 3, respectively. The capacitor element 1, along with the organic electrolyte (not shown), is housed in a cylindrical outer casing 6. The outer casing 6 is made of metals such as aluminum, stainless steel, copper, iron, and brass. The opening of the outer casing 6 is sealed by a sealing member 7. The leads 5a and 5b are led out to the outside by passing through the sealing member 7. The sealing member 7 is made of rubber materials such as butyl rubber.
[0100] The above embodiments describe wound capacitors, but the application scope of the present invention is not limited to the above, and it can also be applied to capacitors of other structures. For example, the application scope of the present invention can also extend to stacked or coin-shaped capacitors.
[0101] (appendix)
[0102] The following technology is disclosed through the above description.
[0103] (Technology 1)
[0104] A capacitor includes a first electrode, a second electrode, and an electrolyte.
[0105] At least one of the aforementioned first electrode and the aforementioned second electrode comprises at least a portion of porous carbon particles covered by a nitrogen-containing carbon material as the electrode active material.
[0106] The aforementioned nitrogen-containing carbon material contains a 6-membered ring.
[0107] The aforementioned 6-membered ring comprises at least one carbonyl carbon atom and at least one of two nitrogen atoms.
[0108] At least a portion of the aforementioned porous carbon particles covered by the aforementioned nitrogen-containing carbon material have micropores with a pore size of 0.7 nm or more and 2 nm or less, and first mesopores with a pore size of more than 2 nm and less than 5 nm.
[0109] The ratio of the first mesopore volume PV2 to the micropore volume PV1 (PV2 / PV1) exceeds 0.57.
[0110] (Technology 2)
[0111] According to the capacitor of technology 1, the aforementioned 6-membered ring comprises at least one selected from the group consisting of isocyanurate ring, triazine ring and 1,3,5-trione ring.
[0112] (Technology 3)
[0113] According to the capacitor of technology 1 or 2, the aforementioned micropore volume PV1 is 0.42 mL / g or more, and the aforementioned first mesopore volume PV2 is 0.25 mL / g or more.
[0114] (Technology 4)
[0115] According to any one of techniques 1 to 3, in the capacitor, at least a portion of the aforementioned porous carbon particles covered by the aforementioned nitrogen-containing carbon material have second mesopores with a pore size exceeding 2 nm and less than 50 nm.
[0116] The ratio of the second mesopore volume PV3 to the total pore volume PVT (PV3 / PVT) is greater than 0.36.
[0117] (Technology 5)
[0118] According to any one of techniques 1 to 4, in the capacitor, at least a portion of the aforementioned porous carbon particles covered by the aforementioned nitrogen-containing carbon material have a first peak in the micropore volume distribution range of more than 0 nm and less than 1 nm, a second peak in the range of more than 1 nm and less than 2 nm, and a third peak in the range of more than 2 nm and less than 5 nm.
[0119] The peak P1 of the aforementioned first peak is located at 1.5cm. 3 In the range of / (g·nm), the peak P2 of the aforementioned second peak is located at 1.0 cm. 3 In the range of / (g·nm), the peak P3 of the aforementioned third peak is located at 1.3cm. 3 The range is above / (g·nm).
[0120] (Technology 6)
[0121] According to the capacitor described in technology 5, when the height of the aforementioned peak P1 is set to HP1, the height of the aforementioned peak P2 is set to HP2, and the height of the aforementioned peak P3 is set to HP3,
[0122] The aforementioned HP1, HP2, and HP3 satisfy the relationship HP1>HP3>HP2.
[0123] (Technology 7)
[0124] The capacitor according to any one of techniques 1 to 6, wherein the nitrogen content C in the aforementioned porous carbon particles, which are at least partially covered by the aforementioned nitrogen-containing carbon material, is... N Less than 3% of the mass.
[0125] (Technology 8)
[0126] According to the capacitor of technology 7, the oxygen content C in the aforementioned porous carbon particles, which are at least partially covered by the aforementioned nitrogen-containing carbon material, is... O Less than 6% of the mass.
[0127] The present invention has been described with respect to preferred embodiments, but such disclosure should not be interpreted restrictively. Various modifications and alterations will undoubtedly be apparent to those skilled in the art upon reading the above disclosure. Therefore, the appended claims should be construed as including all modifications and alterations without departing from the true spirit and scope of the invention.
[0128] Example
[0129] The present disclosure will now be described in detail based on embodiments and comparative examples, but the present disclosure is not limited to the following embodiments.
[0130] [Example 1]
[0131] A wound double-layer capacitor with a rated voltage of 2.7V was manufactured. The specific manufacturing method of the double-layer capacitor is described below.
[0132] (1) Fabrication of porous carbon particles
[0133] 1 part by mass of propylene glycol (as an alkanediol) was added to 15 parts by mass of 2,4-toluene diisocyanate, and the mixture was allowed to cure at room temperature for 24 hours to obtain a crosslinked body. The crosslinked body was then mixed with general-purpose activated carbon to obtain a mixture, which was then heated at 700°C for 0.5 hours under a nitrogen atmosphere to obtain the porous carbon particles of Example 1. It should be noted that the aforementioned mixture contained 20 g of general-purpose activated carbon and 6 g of the aforementioned crosslinked body diluted 200 times with butyl acetate. That is, the concentration C of the aforementioned crosslinked body in butyl acetate was 0.5% by mass. Furthermore, the general-purpose activated carbon had a particle size of 2407 μm. 2 The specific surface area SS is 1.23 cm² / g. 3 The total pore volume PVT is 0.60 cm³ / g. 3 The micropore volume PV1 is 0.34 cm³ / g. 3 The first mesopore volume PV2 is 0.44 cm³ / g. 3 The second mesopore volume PV3 is 2143 nm. As described above, the micropore volume PV1 is the volume of micropores with a pore size of 0.7 nm or more and 2 nm or less. The first mesopore volume PV2, as described above, is the volume of first mesopores with a pore size exceeding 2 nm and less than 5 nm. The second mesopore volume PV3, as described above, is the volume of second mesopores with a pore size exceeding 2 nm and less than 50 nm. It should be noted that the specific surface area SS, total pore volume PVT, micropore volume PV1, first mesopore volume PV2, and second mesopore volume PV3 were measured according to the method described in one of the previous embodiments. Furthermore, the covered porous carbon particles of Example 1 have a pore size of 2143 nm. 2The specific surface area SS is 1.08 cm² / g. 3 The total pore volume PVT is 0.50 cm³ / g. 3 The micropore volume PV1 is 0.33 cm³ / g. 3 The first mesopore volume PV2 is 0.42 cm³ / g. 3 The second mesopore volume PV3 is shown in Table 1 below. Table 1 also shows the ratio of the first mesopore volume PV2 to the micropore volume PV1 (PV2 / PV1) and the ratio of the second mesopore volume PV3 to the total pore volume PVT (PV3 / PVT).
[0134] FT-IR and XPS structural analyses of the porous carbon particle assembly from Example 1 confirmed the presence of CO, C=O, C=N, and CN bonds, and inferred the presence of isocyanurate rings. That is, it is presumed that at least a portion of the porous carbon particles from Example 1 are covered by a nitrogen-containing carbon material.
[0135] For the porous carbon particles covered in Example 1, the nitrogen content C was determined using the method based on JIS M8813:2004. N and oxygen content C O The result was that the nitrogen content C N The oxygen content is 1.1% by mass, C. O The value was 4.2% by mass. In this analysis, an oxygen, nitrogen and hydrogen analyzer (EGMA-830 type manufactured by Horiba Manufacturing Co., Ltd.) was used as the analytical apparatus.
[0136] The differential pore volume distribution of the covered porous carbon particles of Example 1 was determined using known methods. The results are shown below. Figure 2 .Depend on Figure 2 It was confirmed that the porous carbon particles covered in Example 1 have a first peak in the range of more than 0 nm and less than 1 nm, a second peak in the range of more than 1 nm and less than 2 nm, and a third peak in the range of more than 2 nm and less than 5 nm. Furthermore, the peak apex P1 of the first peak was confirmed to be 1.9 cm. 3 For peak values above / (g·nm), the peak P2 of the second peak is 1.1 cm. 3 Above / (g·nm), the peak P3 of the third peak is 1.5m. 3 / (g·nm) or more.
[0137] (2) Fabrication of the electrode (E)
[0138] A slurry was prepared by dispersing 100 parts by weight of porous carbon particles (electrode active material), 10 parts by weight of CMC (binder material), and 10 parts by weight of acetylene black (conductive additive) from Example 1 in an appropriate amount of water. The obtained slurry was coated onto a current collector consisting of an Al foil with a thickness of 30 μm to form a coating film. Next, the coating film was vacuum dried at 110°C and then calendered to form an active layer, thereby obtaining the electrode (E).
[0139] (3) Preparation of organic electrolyte
[0140] An organic electrolyte was prepared by dissolving triethylmethylammonium tetrafluoroborate (an organic salt) in propylene carbonate (a non-aqueous solvent) at a concentration of 1.0 mol / L.
[0141] (4) Fabrication of double-layer capacitors
[0142] A pair of electrodes (E) were prepared and connected with leads to obtain a pair of electrodes (E) with leads. Next, the pair of electrodes (E) with leads were wound around a separator to form a capacitor element. This capacitor element, along with the organic electrolyte, was then placed in a pre-designated outer casing and sealed with a sealing member, thus producing the capacitor of Example 1. Then, an aging treatment was performed at 60°C for 6 hours while applying a rated voltage of 2.5V.
[0143] [Example 2]
[0144] In the mixture, except that 6g of the aforementioned crosslinker was diluted 100 times with butyl acetate, that is, except that the concentration of the aforementioned crosslinker in butyl acetate was 1.0% by mass, the capacitor of Example 2 was prepared in the same manner as in Example 1. Furthermore, the capacitor of Example 2 was subjected to the same aging treatment as in Example 1.
[0145] It should be noted that the porous carbon particles covered in Example 2 have a diameter of 1893 μm. 2 The specific surface area SS is 0.96 cm² / g. 3 The total pore volume PVT is 0.44 cm³ / g. 3 The micropore volume PV1 is 0.30 cm³ / g. 3 The first mesopore volume PV2 is 0.37 cm³ / g. 3 The second mesoporous volume PV3 is shown in g. These results are presented in Table 1 below. Additionally, Table 1 also shows PV2 / PV1 and PV3 / PVT. Furthermore, Figure 2 The results show the determination of the micropore distribution of the covered porous carbon particles in Example 2.
[0146] [Comparative Example 1]
[0147] The capacitor of Comparative Example 1 was fabricated in the same manner as in Example 1, except that general-purpose activated carbon was used instead of the porous carbon particles covering it. Furthermore, the capacitor of Comparative Example 1 underwent the same aging treatment as in Example 1. It should be noted that in the general-purpose activated carbon, the specific surface area SS, total pore volume PVT, micropore volume PV1, first mesopore volume PV2, and second mesopore volume PV3 are as described above. Additionally, the PV2 / PV1 and PV3 / PVT ratios are shown in Table 1 below. Figure 2 The results of the determination of the micropore distribution of the porous carbon particles covered in Comparative Example 1 are shown.
[0148] [Comparative Example 2]
[0149] In the mixture, except that 6g of the aforementioned crosslinker was diluted 50 times with butyl acetate, that is, except that the concentration of the aforementioned crosslinker in butyl acetate was 2.0% by mass, the capacitor of Comparative Example 2 was prepared in the same manner as in Example 1. Furthermore, the capacitor of Comparative Example 2 was subjected to the same aging treatment as in Example 1.
[0150] It should be noted that the porous carbon particles covered in Comparative Example 2 have a diameter of 1626 μm. 2 The specific surface area SS is 0.83 cm² / g. 3 The total pore volume PVT is 0.41 cm³ / g. 3 The micropore volume PV1 is 0.23 cm³ / g. 3 The first mesopore volume PV2 is 0.29 cm³ / g. 3 The second mesoporous volume PV3 is shown in g. These results are presented in Table 1 below. Additionally, Table 1 also shows PV2 / PV1 and PV3 / PVT. Furthermore, Figure 2 The results show the determination of the micropore distribution of the porous carbon particles covered in Comparative Example 2.
[0151] [Comparative Example 3]
[0152] In the mixture, except that 6g of the aforementioned crosslinker was diluted 33 times with butyl acetate, that is, except that the concentration of the aforementioned crosslinker in butyl acetate was 3.0% by mass, the capacitor of Comparative Example 3 was prepared in the same manner as in Example 1. In addition, the capacitor of Comparative Example 3 was subjected to the same aging treatment as in Example 1.
[0153] It should be noted that the porous carbon particles covered in Comparative Example 3 have a diameter of 1354 μm. 2 The specific surface area SS is 0.68 cm² / g. 3 The total pore volume PVT is 0.32 cm³ / g. 3 The micropore volume PV1 is 0.18 cm³ / g. 3 The first mesopore volume PV2 is 0.22 cm³ / g.3 The second mesoporous volume PV3 is shown in g. These results are presented in Table 1 below. Additionally, Table 1 also shows PV2 / PV1 and PV3 / PVT. Furthermore, Figure 2 The results show the determination of the micropore distribution of the porous carbon particles covered in Comparative Example 3.
[0154] [Comparative Example 4]
[0155] In the mixture, except that 6g of the aforementioned crosslinker was diluted 20 times with butyl acetate, that is, except that the concentration of the aforementioned crosslinker in butyl acetate was 5.0% by mass, the capacitor of Comparative Example 4 was prepared in the same manner as in Example 1. In addition, the capacitor of Comparative Example 4 was subjected to the same aging treatment as in Example 1.
[0156] It should be noted that the porous carbon particles covered in Comparative Example 4 have a diameter of 1179 μm. 2 The specific surface area SS is 0.60 cm² / g. 3 The total pore volume PVT is 0.28 cm³ / g. 3 The micropore volume PV1 is 0.13 cm³ / g. 3 The first mesopore volume PV2 is 0.17 cm³ / g. 3 The second mesoporous volume PV3 is shown in g. These results are presented in Table 1 below. Additionally, Table 1 also shows PV2 / PV1 and PV3 / PVT. Furthermore, Figure 2 The results show the determination of the micropore distribution of the porous carbon particles covered in Comparative Example 4.
[0157] [Table 1]
[0158]
[0159] [evaluate]
[0160] Initial Capacity
[0161] For the capacitors in each example (Examples 1-2 and Comparative Examples 1-5), they were charged with a constant current of 100 mA / g at room temperature (23±2°C) until the voltage reached 2.7V, and then the applied voltage of 2.7V was maintained for 7 minutes. Then, they were discharged with a constant current of 100 mA / g at room temperature until the voltage reached 0V.
[0162] In the above discharge, the time t (seconds) required for the voltage to drop from 2.16V to 1.08V was measured. It should be noted that 2.16V is equivalent to 80% of 2.7V (the voltage at full charge), and 1.08V is equivalent to 40% of 2.7V. Using the measured time t, the initial capacitance C1(F) before the float charge test was calculated for each example capacitor according to the following formula (A).
[0163] Initial capacity C1 = Id × t / ΔV1……(A)
[0164] It should be noted that in formula (A), Id is the current value calculated from 100mA / g and the mass (g) of the electrode active material, and ΔV1 is the value obtained by subtracting 1.12V from 2.16V.
[0165] <Initial Resistance>
[0166] Using the discharge curve obtained through the above discharge (vertical axis: discharge voltage, horizontal axis: discharge time), an approximate straight line is obtained within the range of 0.5 seconds to 2 seconds from the start of discharge. The intercept voltage VS of this approximate straight line is then calculated. Next, the value (V0-VS) obtained by subtracting the voltage VS from the voltage V0 at the start of discharge (0 seconds after the start of discharge) is calculated as ΔV2. Using ΔV2 (V) and the discharge current value Id (the current value calculated from 100 mA / g and the mass (g) of the electrode active material), the internal resistance (DCR) R1 (Ω) of the capacitor before the float charge test is calculated using the following formula (B).
[0167] Internal resistance R1 = ΔV2 / Id……(B)
[0168] <Float Charging Test>
[0169] Prepare four capacitors for each of the examples (Examples 1-2 and Comparative Examples 1-5). Then, charge the four capacitors at a constant current of 100 mA / g at 50°C until the voltage reaches 2.7V. Next, maintain the 2.7V voltage for each of the four capacitors for a specified time (92h, 230h, 536h, and 1060h). Thus, the four capacitors are stored at a voltage of 2.7V at specified intervals. Then, for each of the four capacitors maintained for the specified time, discharge them at a constant current of 100 mA / g at 50°C until the voltage reaches 0V.
[0170] Then, similar to the determination of capacitance and internal resistance before the float charge test, the four capacitors in each example were charged and discharged at room temperature, and the capacitance and resistance were calculated after 92 hours, 230 hours, 536 hours, and 1060 hours, respectively. The measured values of capacitance are shown in Table 2A below, and the measured values of resistance are shown in Table 2B below. In addition, for 92 hours, 230 hours, 536 hours, and 1060 hours, the capacitance retention rate and resistance increase rate relative to the initial value were calculated. The capacitance retention rate is the relative value of capacitance at each time point with the initial capacitance set to 100%, and the resistance increase rate is the relative value of resistance at each time point with the initial resistance set to 100%. The capacitance retention rate is shown in Table 2C below, and the resistance increase rate is shown in Table 2D below.
[0171] [Table 2A]
[0172]
[0173] [Table 2B]
[0174]
[0175] [Table 2C]
[0176]
[0177] [Table 2D]
[0178]
[0179] As shown in Tables 2A to 2D, the capacitors in each embodiment (Examples 1 and 2) have relatively high initial capacitance, exceeding 120 F / g, and retain approximately 80% of their capacitance even after 1060 hours. Furthermore, the capacitors in each embodiment have low initial resistivity, below 0.80 Ω, and exhibit a low value of less than 1 Ω even after 1060 hours, with the resistance increase rate remaining at approximately 20%. In contrast, the capacitor in Comparative Example 1 has relatively high initial capacitance, exceeding 133 F / g, and retains approximately 80% of its capacitance even after 1060 hours, but its initial resistance exceeds 0.9 Ω and exceeds 1 Ω after 1060 hours. Similarly, the capacitor in Comparative Example 2 has relatively high initial capacitance, around 120 F / g, and retains approximately 80% of its capacitance even after 1060 hours, but its initial resistance exceeds 1.0 Ω and becomes 1.2 Ω after 1060 hours. Furthermore, it can be seen that in the capacitors of Comparative Examples 3 to 5, the initial capacitance, initial resistance, capacitance retention rate, and resistance increase rate are all far worse than those of the capacitors of Examples 1 and 2.
[0180] Industrial availability
[0181] The capacitor disclosed herein can be used in applications requiring both the ability to maintain capacitance over a long period of time and to suppress the rise of internal resistance.
[0182] Explanation of reference numerals in the attached figures
[0183] 1: Capacitor element; 2: First electrode; 3: Second electrode; 4: Separator; 5a, 5b: Lead wires; 6: Outer casing; 7: Sealing component; 10: Capacitor.
Claims
1. A capacitor comprising a first electrode, a second electrode, and an electrolyte. At least one of the first electrode and the second electrode comprises at least a portion of porous carbon particles covered by a nitrogen-containing carbon material as the electrode active material. The nitrogen-containing carbon material contains a 6-membered ring. The 6-membered ring comprises at least one of one carbonyl carbon and two or more nitrogen atoms. At least a portion of the porous carbon particles covered by the nitrogen-containing carbon material have micropores with a pore size of 0.7 nm or more and 2 nm or less, and first mesopores with a pore size of more than 2 nm and less than 5 nm. The ratio of the first mesopore volume PV2 to the micropore volume PV1, i.e., PV2 / PV1, exceeds 0.
57.
2. The capacitor according to claim 1, wherein, The 6-membered ring comprises at least one selected from the group consisting of isocyanurate rings, triazine rings, and 1,3,5-trione rings.
3. The capacitor according to claim 1 or 2, wherein, The micropore volume PV1 is 0.42 mL / g or more, and the first mesopore volume PV2 is 0.25 mL / g or more.
4. The capacitor according to claim 1 or 2, wherein, The porous carbon particles, at least a portion of which are covered by the nitrogen-containing carbon material, have second mesopores with a pore size exceeding 2 nm and less than 50 nm. The ratio of the second mesopore volume PV3 to the total pore volume PVT, i.e., PV3 / PVT, exceeds 0.
36.
5. The capacitor according to claim 1 or 2, wherein, The porous carbon particles, at least partially covered by the nitrogen-containing carbon material, exhibit a first peak in the micropore volume distribution range exceeding 0 nm and less than 1 nm, a second peak in the range above 1 nm and below 2 nm, and a third peak in the range exceeding 2 nm and below 5 nm. The peak P1 of the first peak is located at 1.5cm. 3 In the range of / (g·nm), the peak P2 of the second peak is located at 1.0 cm. 3 In the range of g·nm and above, the peak P3 of the third peak is located at 1.3 cm. 3 The range is above / (g·nm).
6. The capacitor according to claim 5, wherein, When the height of peak P1 is set to HP1, the height of peak P2 is set to HP2, and the height of peak P3 is set to HP3, HP1, HP2, and HP3 satisfy the relationship HP1>HP3>HP2.
7. The capacitor according to claim 1 or 2, wherein, In the porous carbon particles that are at least partially covered by the nitrogen-containing carbon material, the nitrogen content C N Less than 3% of the mass.
8. The capacitor according to claim 7, wherein, In the porous carbon particles that are at least partially covered by the nitrogen-containing carbon material, the oxygen content C O Less than 6% of the mass.
Citation Information
Patent Citations
Electric double-layer capacitor and manufacture thereof
JP1997063905A
Method for manufacturing active carbon for electric double-layer capacitor, and electric double-layer capacitor using the same
JP2004031713A
Active carbon for electrode material and energy storage device
JP2010003940A
Electrochemical capacitor
JP2010114356A
Determination device, pattern formation device, and method for manufacturing article
JP2024041389A